Meyerbeer's les huguenots : an evangel of religion and love - Letellier, Robert Ignatius (Cambridge Scholars Publishing, 2014)
On 29 February 1836, Les Huguenots, a grand opera by Giacomo Meyerbeer (1791-1864), with words by Eugène Scribe (1791-1861) and Émile Deschamps (1791-1871), was performed for the first time, at the Paris Opéra. It was to be one of the most successful productions ever staged at the Opéra, with 1,126 performances in Paris over the next hundred years, and, in the process, breaking all box office records. It became Meyerbeer's most popular work, with thousands of stagings throughout the world. L...
Keywords: Operas : Librettos; Operas : Literary themes, motives